Mengintegrasikan Kearifan Lokal dan Teknologi: Bahan Ajar Scan to Learn pada Materi Teorema Pythagoras - Samuel Igo Leton (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2026)
Mathematical literacy is an important competency because it helps students formulate, use, and interpret mathematics in real-life contexts. However, the teaching of the Pythagorean theorem still frequently emphasizes formula memorization and procedures, causing students to struggle with understanding its geometric meaning, representations, and application in contextual problems. This study aims to develop Scan to Learn teaching materials integrated with local wisdom and Augmented Reality on the topic of the Pythagorean theorem to improve students' mathematical literacy. The study employed a Research and Development approach using the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. The research subjects were 25 eighth-grade students at Adisucipto Junior High School in Kupang City, with instruments consisting of validation sheets, teacher and student response questionnaires, mathematical literacy tests, and student activity observation sheets. The results showed that the teaching materials obtained a mean validation score of 3.45, categorized as very good. Student responses reached 96.93% and teacher responses reached 96%, placing the product in the very practical category. In terms of effectiveness, all students achieved mastery with a mean post-test score of 87.76 and an N-Gain of 0.62, categorized as moderate. The Scan to Learn teaching materials based on local wisdom and Augmented Reality are deemed suitable for use as a contextual, visual, and meaningful alternative for learning Pythagoras. This product contributes to strengthening mathematical literacy by connecting mathematical concepts with local culture and interactive visualization.